Electrical Pulse Induced One‐step Formation of Atomically Dispersed Pt on Oxide Clusters for Ultra‐Low‐Temperature Zinc‐Air Battery. (17th November 2022) - Ye, Chenliang; Zheng, Meng; Li, Zhiming; Fan, Qikui; Ma, Haiqing; Fu, Xianzhu; Wang, Dingsheng; Wang, Jin; Li, Yadong
Abstract: Atomically dispersed sites anchored on small oxide clusters are attractive new catalytic materials. Herein, we demonstrate an electrical pulse approach to synthesize atomically dispersed Pt on various oxide clusters in one step with nitrogen‐doped carbon as the support (Pt1 −MO x /CN). As a proof‐of‐concept application, Pt1 −FeO x /CN is shown to exhibit high activity for oxygen reduction reaction (ORR) with a half‐wave potential of 0.94 V vs RHE, in contrast to the poor catalytic performance of atomically dispersed Pt on large Fe2 O3 nanoparticles. Our work has revealed that, by tuning the size of the iron oxide down to the cluster regime, an optimal OH* adsorption strength for ORR is achieved on Pt1 −FeO x /CN due to the regulation of Pt−O bonds. The unique structure and high catalytic performance of Pt1 −FeO x /CN enable the Zinc‐Air batteries an excellent performance at ultralow temperature of −40 °C with a high peak power density of 45.1 mW cm −2 and remarkable cycling stability up to 120 h. Abstract : An electrical pulse approach is employed to obtain dispersed Pt on diverse oxide clusters in one step with nitrogen‐doped carbon being the support. As a proof‐of‐concept application, Pt1 −FeO x /CN enables the zinc‐air batteries to achieve an excellent electrochemical performance at an ultralow temperature of −40 °C.